Conceptual approaches to the formation of an automated system of management of the land and property complex of the National academy of agrarian sciences of Ukraine - Novakovsky, L.; Dorosh, Y.; Tarnopolskyi, A.; Ibatullin, S. (Land Management, Cadastre and Land Monitoring, 2019)
The importance of creation and improvement of the automated system of management of the land and property complex of the National Academy of Agrarian Sciences of Ukraine is substantiated. The principles and standards of national geospatial data infrastructure are emphasized.The following are the main components of the automated system of land and real estate management of NAAS: object composition of data, roles and levels of access to the system, data protection and information security, business processes and functionality, spatial and organizational structure, data quality, retrospect, data analysis and reporting, planning and vision, etc.There are several subject blocks of business processes of managing the objects of the NAAS land and property complex: determination of the legal status and ensuring control over the observance of the legal regime of the use of land resources and real estate; research and experimental development; production, economic, service and support processes; monitoring, analysis and reporting; interaction with other services and interoperability of data; verification and validation of data.Among the main tasks of the system: geoinformation database of real rights to real estate and their restrictions, inventory and monitoring of land resources, forming of agricultural land, accounting for particularly valuable land, zoning and zoning, etc.When considering approaches to the formation of the automated system, the peculiarities of the research and educational purpose of the NAAS land and property complex and its importance for the national security of the country are taken into account.